Effects of a six-week strength training programme on change of direction performance in youth team sport athletes - Bourgeois, F. A.; Gamble, P.; Gill, N. D.; McGuigan, M. R. (Sports, 2017)
This study investigated the effects of eccentric phase-emphasis strength training (EPE) on unilateral strength and performance in 180- and 45-degree change of direction (COD) tasks in rugby union players. A 12-week cross-over design was used to compare the efficacy of resistance training executed with 3 s eccentric duration (EPE, n = 12) against conventional strength training, with no constraints on tempo (CON, n = 6). Players in each condition were categorised as `fast` (FAST) or `slow` (SLOW) using median trial times from baseline testing. Players recorded greater isometric strength improvements following EPE (ES = -0.54 to 1.80). Whilst these changes were not immediate, players improved in strength following cessation. Improvements in 180-degree COD performance was recorded at all test-points following EPE (ES = -1.32 to -0.15). Improvements in 45-degree COD performance were apparent for FAST following CON (ES = -0.96 to 0.10), but CON was deleterious for SLOW (ES = -0.60 to 1.53). Eccentric phase-emphasis strength training shows potential for sustained strength enhancement. Positive performance changes in COD tasks were category- and condition-specific. The data indicate the greatest improvement occurred at nine weeks following resistance training in these players. Performance benefits may also be specific to COD task, player category, and relative to emphasis on eccentric phase activity